Performance of State Civil Services at the Population and Civil Registration Services Of Bulukumba District - ranreng; Nurdin Nara; Muh Tang Abdullah (Enrichment : Journal of Management, 2022)
This study aims to describe and analyze the performance of the state civil apparatus (study of the Population and Civil Registration Office of Bulukumba Regency) to describe and analyze the factors that influence the performance of the state civil apparatus at the population and civil registration office of Bulukumba Regency. This research was carried out at the Population and Civil Registration Office of Bulukumba Regency. This type of research is a qualitative research to analyze events in the field and match the existing theory with a case study approach. Data collection techniques are through observation, interviews and documentation. The results showed: The performance of the State electoral apparatus in the Population and Registration Service of Bulukumba Regency as seen from the elements: Productivity, Service Quality, Responsiveness and Accountability has looked good. encourage the creation of performance providing opportunities for subordinates, competence, commitment and motivation factors can support so that the performance of the state civil apparatus in the future can be improved.”